Psiko-Sosio-Edukasi sebagai Upaya Optimalisasi Peran Remaja dalam Pencegahan Seks Bebas - Kustin Kustin; Yuni Handayani (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
The transition period between children and adults is a development in an individual's life, one of which is changes in himself. Both physical and psychological changes that occur can give rise to a desire to have sex during adolescence.The sex in adolescents often occurs outside the marriage relationship or is done freely. If this period is not developed properly, problems such as violation and neglect of values will arise. Free sex can cause negative effect such as unwanted pregnancy, abortion, sexually transmitted diseases, illegal drug use, and HIV/AIDS. To minimize these activities, it is necessary to increase the role of adolescents through socio-psycho education provided to adolescents. This community service activity aims to increase adolescents' role in preventing free sex through a psycho-socio-educational approach. This activity was carried out on a group of 109 Vocational High School children. The location of service is Vocational High School dr. Soebandi Jember. The activity held between March and May 2023. The results of their behavioral activities in efforts to prevent free sex by improving relationships with parents and adolescents, skills to resist negative pressure, increasing adolescent religion level by properly regulating media use, especially pornography, health education for adolescents involving the role of school and their families. It is expected that activities like this will continue to be carried out to increase promotive and preventive efforts in preventing free sex in adolescents and modifying other activities.